The Effect of Household Air Pollution Exposure on the Incidence of Acute Respiratory Infection in Children Under Five in Asia: A Meta-Analysis (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
ASIA is a continent with many people who still have and use biomass or solid fuel use (SFU) for cooking and various household air pollution. Previous research has mentioned the negative effects of household air pollution on the incidence of acute respiratory infections in children under 5 years. Acute respiratory diseases have even become the cause of at least 4 million deaths of children under 5 years old every year in the world. The meta-analysis aimed to estimate the correlation between household air pollution and the incidence of acute respiratory infections in children under five in ASIA. This study was a meta-analysis. Primary data is taken through the electronic databases such as: PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords "Household air pollution AND acute respiratory tract infections AND adjusted odds ratio", "indoor air pollution AND acute respiratory tract infections AND adjusted odds ratio", and "paparan asap rumah tangga DAN ISPA DAN adjusted odds ratio". Articles taken between 2013-2023. Statistical analysis was performed using the RevMan 5.3. 7 articles qualified for quantitatively analysis. The exposure of household air pollution can increases the risk of acute respiratory infections 3 times in children under five and statistically significant (OR 3.36; 95% CI: 2.96 – 3.81; p value < 0.001). Exposureto household air pollution is a significant risk factor for the incidence of acute respiratory infections in children under 5 years.